Nexus among Irregular Payment of Modulated Salary, Teachers’ Productivity and General Welfare in Osun State, Nigeria (World Journal of Vocational Education and Training, 2020)
The study examined the nexus among irregular payment of modulated salary, teachers’ productivity and general welfare in Osun State, Nigeria. Descriptive research design was adopted and two-hundred (200) participants were sampled. Structured questionnaire tagged ‘Modulated Salary Structure Teachers’ Productivity and Welfare Questionnaire’ (MSSTPWQ) was used. Both inferential and descriptive statistical tools were used for data analysis. The empirical findings indicated that the irregular payment of modulated salary did not prevent serving teachers under consideration from being productive but they were unable to meet up with some of their welfare-enhancing targets. It was further revealed that there was no significant difference between male and female teachers’ level of productivity during irregular payment of modulated salary. Besides, a significant difference was discovered between teachers’ level of productivity based on school location but in favour of teachers serving in urban schools. On the part of welfare, the outcomes indicated that there was no significant difference in the teachers’ welfare level during irregular payment of modulated salary when gender and school location were considered. As a result, it was recommended that, employers should desist from applying contractionary wage policy during financial crisis, bush allowances should be introduced for those employees working in rural areas, employees in teaching industry are advised to enforce the professional ethics of their job and the need for financial institutions or other lending houses to review the mode of loan repayment in order to lessen the employees’ debt burden during the period of servicing the loan among others.